Enhancing Sociolinguistic Competence through Language Environment: The Role of Visual and Interactive Exposure - wadi, Namlul; Abidin, Munirul; Yurisa, Penny Respati; Farisandi, Farisandi; Maulidi, Ilham (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
This study investigates the causal impact of language environment components specifically Visual Exposure Intensity and Interactive Exposure Intensity on the sociolinguistic competence of students at TMI (Tarbiyatul Mu'allimien al-Islamiyah) Al-Amien Prenduan Islamic Boarding School. Utilizing a quantitative Ex-Post Facto design with Path Analysis on 310 respondents, the research deconstructs the